Why Diamonds and De Beers?, or The Need for Accumulation Studies - David Troy Cochrane (Forum on Capital As Power - Toward a New Cosmology of Capitalism, 2016)
The text of this paper served as the introductory presentation for my PhD defence, held on December 2015. In it, I explain what I tried to do with the dissertation, the methods I used, and the larger project I hope it is initiating. Specifically, I suggest there is a need for accumulation studies as a field of research and analysis. The dissertation was a case study within this not-yet-existent field. Hopefully, this text serves to clarify my approach and, ideally, will generate greater interest in such research.
Keywords: 330; accumulation studies; De Beers; diamonds